Kurikulum dan Dinamika Perubahannya di Pondok Pesantren Universitas Islam Indonesia Yogyakarta. - Rizka Amalia Shofa (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
This paper is intended to express the concept and dynamics of curriculum change of Pondok Pesantren Universitas Islam Indonesia. The importance of the problem discussed is related to curriculum that is used by Pondok Pesantren as one of the foundations of the development of Islamic educational institutions that would potentially affect the development of Islamic education in Indonesia in general. The concept of curriculum which is applied does not follow the national curriculum that is used at school or college. The result of the research showed that there is a change in the destination and setting of the curriculum of Pondok Pesantren Universitas Islam Indonesia that referred to Universitas Islam Indonesia’s aim to be World Class University. The change affected the content of the curriculum, teaching materials, and the learning methods. A change impact on the activity of students who are not only prepared to be a mujtahid, but more geared to hone the ability of thinking and researching.